2018
DOI: 10.7812/tpp/17-138
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment, Contents, and Retweets: A Study of Two Vaccine-Related Twitter Datasets

Abstract: Engaging social media key opinion leaders to facilitate health education about vaccination in their tweets may allow reaching a wider audience online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
74
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 28 publications
8
74
0
3
Order By: Relevance
“…Our findings suggest a possibility of divergent interests between countries of different levels of economic development with regard to the types of HIV/AIDS-related information being shared on Twitter. These results echo observations that social media users reacted to infectious disease outbreaks differently between different communities or countries [7,8]. However, since location data is self-reported, and country-level income data does not apply to individuals (ecological fallacy), the authors caution against over-interpretation of the results of this exploratory study.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Our findings suggest a possibility of divergent interests between countries of different levels of economic development with regard to the types of HIV/AIDS-related information being shared on Twitter. These results echo observations that social media users reacted to infectious disease outbreaks differently between different communities or countries [7,8]. However, since location data is self-reported, and country-level income data does not apply to individuals (ecological fallacy), the authors caution against over-interpretation of the results of this exploratory study.…”
Section: Discussionsupporting
confidence: 77%
“…Social media analysis revealed users' reactions to specific health promotion events [6]. Users from different countries might react to the same disease differently [7,8]. Research comparing Twitter contents of five different languages pertinent to the MERS outbreak in South Korea in 2015 found that users from different Asian countries had different concerns about the outbreak [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 11 Research from large datasets of vaccine-related tweets shows that anti-vaccine tweets are retweeted over 4 times more frequently than neutral tweets, while pro-vaccine tweets are retweeted one-and-a-half times more frequently. 11 Antivaccine tweets more frequently mention the risks or dangers of vaccines and distrust of scientific organizations and government. 11 For pro-vaccine tweets, the most common themes appear to be related to global vaccination efforts, scientific organizations, the efficacy of vaccines, and outbreaks that could have been prevented by vaccines.…”
Section: Introductionmentioning
confidence: 99%